2021
DOI: 10.1088/2053-1583/abd6b6
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of interlayer stacking orders and rotations in bilayer PtSe2 visualized by STEM

Abstract: Understanding the evolution mechanisms of interlayer stacking structures, particularly at the atomic scale, is of great significance for modulating the physical properties and realizing the full potential of 2D materials in electronics and quantum information applications. Herein, by performing in situ experiments using aberration corrected scanning transmission electron microscopy, the evolution of diverse interlayer stacking sequences (from 3R to N, N to 3R and N(3R) to AB′-stacked) in bilayer PtSe2 are dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…2L ′ samples are a noticeable exception, with a singular Raman signature differing from the one of 2L (detailed comparison in figure SM4). In fact, the comparison of absorption behavior with DFT predictions for 2L ′ suggests an AB stacking [12], which has been theoretically identified as a stable phase for 1T − PtSe 2 [5,12,30,34], and is a common defect in grown films [35,36].…”
Section: Atomic Structure Signaturementioning
confidence: 99%
“…2L ′ samples are a noticeable exception, with a singular Raman signature differing from the one of 2L (detailed comparison in figure SM4). In fact, the comparison of absorption behavior with DFT predictions for 2L ′ suggests an AB stacking [12], which has been theoretically identified as a stable phase for 1T − PtSe 2 [5,12,30,34], and is a common defect in grown films [35,36].…”
Section: Atomic Structure Signaturementioning
confidence: 99%
“…[ 21 ] observed 1H/1T in‐plane PtSe 2 heterostructures at different annealing temperatures, while Xu et al. [ 28 ] obtained trigonal prismatic bilayer PtSe 2 .…”
Section: Introductionmentioning
confidence: 99%
“…[25] PtSe 2 has been observed in different coordination phases: For instance, Wang et al [26] showed the formation of MoS 2 -like 2H-PtSe 2 nanoflakes by chemical vapor deposition at 900 °C, while Tong et al [27] reported that single-layer of the same material was formed by liquid immersion of Pt(111) in Na 2 Se. Furthermore, Lin et al [21] observed 1H/1T in-plane PtSe 2 heterostructures at different annealing temperatures, while Xu et al [28] obtained trigonal prismatic bilayer PtSe 2 .…”
Section: Introductionmentioning
confidence: 99%
“…The recent exploration of the twisted bilayer (BL) two-dimensional (2D) system was initiated in graphene [1][2][3][4] and soon extend to TMDC [5][6][7] and other 2D materials [8][9][10]. The twisted 2D system leads to various intriguing properties, such as unconventional superconductivity [2,11], Mott insulator and flat bands [1,4], Hofstadter's butterfly spectra [12,13], moiré excitons [14][15][16], piezoelectric networks [17], quasicrystalline [18] and thus open a new research area known as twistronics [19][20][21].…”
Section: Introductionmentioning
confidence: 99%